China’s Academic Excellence Initiatives - Cao, Yannan; Yang, Rui (International Higher Education, 2023)
China is often cited as a classic example of successful academic excellence initiatives featured by a prominent role of the government. Their next stage of development needs to explore new models to support innovation and sustainability in higher education.